PENENTUAN PRIORITAS PEMBANGUNAN SUB SEKTOR PERTANIAN TERHADAP SEKTOR PERTANIAN DI KABUPATEN PARIGI MOUTONG - I Gede Laksana Wibawa; Yulianti Kalaba; Alimudin Laapo (Agroland: Jurnal Ilmu-ilmu Pertanian, 2018)
This research aimed to determine the agriculturalbasis sub-sector, to analyseagricultural specialization sub-sector, to analyseagricultural sub-sector performances, and to determine priorities of agricultural sub-sector development. Data analysis tools used in this research were location quotient (LQ) analysis, growth ratio model (MRP), overlay, shift share Esteban Marquillas (SS-EM), and sectorial typology. The contribution criteria in the LQ analysis show that cropshave become agricultur albasis sub-sector.Based on the growth criteria,the analysis of MRP produces positive growth rate on crops,forestry and logging sub-sectors.  The overlay analysis shows that the food cropshavebecome the agricultural basis sub sector. The analysis of SS-EM indicates that only food crop sub-sector has competitive and specialized advantage in Parigi Moutong district. The sectorial typology analysis suggests that the priority agricultural sub sectors belong to food crops, horticulture, forestry, and fishery whereas the potential sub sectors are plantation and agricultural services.  Livestock is a developing sub sector.   The food crops sub sector is the main priority in the agricultural sector development in Parigi Moutong district because this sub sector contribute largely to the agricultural sector and it has positive growth, specialization and highly competitive in both district and province levels.  It is also the priority sub sector with higher contribution to Central Sulawesi development.Keywords:Agricultural sub-sector, basis sector, contribution, and growth rate.